Public Investment in a Production Network: Aggregate and Sectoral Implications - Peri, Alessandro; Rachedi, Omar; Varotto, Iacopo (The Review of Economics and Statistics, 2026)
Aggregate and sectoral effects of public investment crucially depend on the interaction between the output elasticity to public capital and intermediate inputs. We uncover this fact through the lens of a New Keynesian production network. This setting doubles the socially optimal amount of public capital relative to the one-sector model without intermediate inputs, leading to a substantial amplification of the public-investment multiplier. We also document novel sectoral implications of public investment. Although public investment is concentrated in far fewer sectors than public consumption, its effects are relatively more evenly distributed across industries. We validate this model implication in the data.